ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN TINDAKAN PENCEGAHAN PROTOKOL COVID-19 PADA PENUMPANG KAPAL CEPAT PELABUHAN NUSANTARA KOTA KENDARI - Ermawati Rahim; La Ode Muh. Sety; Ramadhan Tosepu; Adius Kusnan (NHM PRESS, 2021)
Strict supervision and control of public transportation modes is one of the new platforms for the occurrence of COVID-19 cases. One of them is sea transportation modes such as ships that carry many people in a limited space with relatively homogeneous mixing over a longer period of time than other modes of transportation. Changes in the behavior of ship passengers regarding preventive measures are very important to inhibit the spread of COVID-19. This change can be seen from the number of ship passengers who comply with government regulations to implement health protocols. Judging from the number of COVID-19 cases on November 16, 2020, Kendari City is the area with the highest number of confirmed positive COVID-19 cases, with 3055 cases. The purpose of this study was to determine the knowledge of fast ship passengers at the Nusantara port towards the COVID-19 health protocol prevention measures, to determine the attitude of the Nusantara fast boat passengers to the COVID-19 health protocol prevention measures, the confidence of the Nusantara port fast boat passengers to the COVID-19 health protocol prevention measures 19, knowing the relationship between facilities and infrastructure on fast boats at the Nusantara port to the preventive measures for the COVID-19 health protocol, and knowing the relationship between the personal hygiene of passengers on the fast boats at the Nusantara port and the preventive measures for the COVID-19 health protocol. This type of research is correlational research. The population of this research is the number of passengers on the fast boat at Pelabuhan Nusantara per day as many as 400 people. The research sample was 384 people. The results showed that the 5 variables studied, which had a relationship with the preventive measures for the COVID-19 health protocol were knowledge of passengers, p-value = 0.000, passenger attitudes, p-value = 0.000, passenger confidence, p-value = 0.000. , ship facilities and infrastructure obtained p-value = 0.002, and personal hygiene of passengers obtained p-value = 0.032.